ANALISIS PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, RISIKO PASAR, DAN INFLASI TERHADAP NILAI PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS - Aldi Patria Said (2022)
This study aims to identify the effect of Sales Growth, Profitability, Market Risk, and Inflation on Firm Value. The population used in this study is Consumer Non-Cyclicals sector companies on the IDX in 2017-2021 period. By purposive sampling, 295 samples were obtained in this study. The data analysis technique used is the Generalized Method of Moments (GMM) using the Eviews 12 program. Partially, the results of this study indicate that Sales Growth proxied by Sales Growth has no effect on firm value, Profitability proxied by Return on Assets has a positive effect on company value, Market Risk which is proxied by Beta has a negative effect on company value, and Inflation which is proxied by Inflation has a negative effect on company value. Simultaneously, the variable Sales Growth, Profitability, Market Risk, and Inflation have an effect on Firm Value.